Stock-Flow Adjustments and Fiscal Transparency : A Cross-Country Comparison - Weber, Anke (IMF Working Papers; Working Paper ;, 2012)
Over the past three decades, large and persistent discrepancies between the annual change in public debt and the budget deficit, so-called stock-flow adjustments, were a prominent feature of debt dynamics in many economies. The aim of this paper is to investigate the underlying determinants of such discrepancies and their relationship with fiscal transparency using data for 163 countries. Results show that such discrepancies can only be partly explained by balance sheet effects and the realization of contingent liabilities and that significant differences exist in average stock-flow adjustments across countries reflecting country-specific factors. The more fiscally transparent the country, the smaller these tend to be. The contribution of stock-flow adjustments to increases in debt is likewise smaller in countries with above average fiscal transparency. This may not be coincidental, as a lack of fiscal transparency may make it easier for governments to engage in deceptive fiscal stratagems.